2018
DOI: 10.1200/po.17.00235
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofMDM2Amplification: Next-Generation Sequencing of Patients With Diverse Malignancies

Abstract: Purpose MDM2 amplification can promote tumorigenesis directly or indirectly through p53 inhibition. MDM2 has increasing clinical relevance because inhibitors are under evaluation in clinical trials, and MDM2 amplification is a possible genomic correlate of accelerated progression, known as hyperprogression, after anti–PD-1/PD-L1 immunotherapy. We used next-generation sequencing (NGS) to ascertain MDM2 amplification status across a large number of diverse cancers. Methods We interrogated the molecular profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…In a large study of 102,878 patients with different malignancies, NGS of tumor tissue revealed MDM2 amplification in 3.5% of cases [41]. Tumors exhibiting MDM2 amplification were less often associated with a high TMB than MDM2 wild-type tumors [41].…”
Section: Discussionmentioning
confidence: 99%
“…In a large study of 102,878 patients with different malignancies, NGS of tumor tissue revealed MDM2 amplification in 3.5% of cases [41]. Tumors exhibiting MDM2 amplification were less often associated with a high TMB than MDM2 wild-type tumors [41].…”
Section: Discussionmentioning
confidence: 99%
“…There are inconsistencies between studies in that some have not shown age or sex to be predictors. Furthermore, although it has been described by several groups including ours , the putative genomic correlates (e.g., MDM2/MDM4 and EGFR alterations) require larger sample size validation and an understanding of potential mechanisms by which these alterations could mediate or facilitate accelerated tumor growth after checkpoint blockade.…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 91%
“…Matos et al [13] TTF <2 months and minimum increase in measurable lesions of 10 mm plus (A) increase of ≥40% in target tumor burden compared with baseline or (B) increase ≥20% in target tumor burden plus multiple new lesions HPD was not associated with age, tumor type, checkpoint inhibitor regimens, previous checkpoint inhibitor, or metastatic site ours [10,12,19,34], the putative genomic correlates (e.g., MDM2/MDM4 and EGFR alterations) require larger sample size validation and an understanding of potential mechanisms by which these alterations could mediate or facilitate accelerated tumor growth after checkpoint blockade.…”
Section: Female Gendermentioning
confidence: 99%
“…In a molecular profiling study of 102,878 patients, this same group identified the amplification of MDM2 in 3.5%, with large variations among tumor types (63.6% in liposarcoma and <1% in thyroid carcinoma and adenocarcinoma of colon and rectum). Interestingly most patients with MDM2 amplification had a low Tumor Mutational Burden (54).…”
Section: Factors Predictive Of Hyperprogressionmentioning
confidence: 99%